Dilemma of the Kinship and Formality Relationship between Employer and Domestic Worker in Yogyakarta, Indonesia - Muryanti, Muryanti (KOMUNITAS: International Journal of Indonesian Society and Culture, 2015)
Labor relations between employers and domestic workers is one of the very old form of relationship that is influenced by cultural and social development of society. The purpose of this study to determine the forms of employment relationships of kinship and formal working relationships and form working relationships between them are preferred by employers in Yogyakarta. The theory used in this study uses the concept of patron-client (Scott, 1985) and patriarchy (Delaney, 2005) to explain the two forms of the employment relationship in the domestic sphere. This research used post-positivist paradigm with mixed methods, quantitative and qualitative (Guba & Lincoln, 1997). The results showed kinship relationships occur in household domestic worker, working full time and living in the employer’s home. Formal relationship occurs in the working relationship of domestic workers work part time (fill-in), a special work as pramurukti and/ baby sitter. Generally, employers prefer that is kinship relationship because of the perspective domestic worker are part of the family. In contrast, domestic worker prefer to work part-time, work-specific and do not live in private homes because more wages and freely in the work. Employers and domestic workers have individual rationality in determining the form of employment relationship. In fact, kinship relationships wane and increasing the quantity of formal relations, characterized by the use of part-time domestic worker are increasingly numerous. In essence, kinship relationships and have in common that formal work status and low wages.